Bridging Technology and Language Learning: Vocational Students’ Perceptions of Wordwall in ELT - Rara Raudhah Sakha Mahardika; Soviyah Soviyah; Eryke Sukma Widiarna (PAEDAGOGIA, 2025)
This study explores the students’ perceptions or responses to the use of Wordwall as learning media in English learning activities. It focused on ease of use, impact on motivation, material comprehension, vocabulary improvement and challenges as well as future plan with it. Conducted in August 2024 in one public vocational school located in the suburban area of Yogyakarta, Indonesia, it involved 21 vocational school students specializing in fashion design. The research adopted survey-based research. The research instrument was a questionnaire containing both closed and open ended questions. The collected data were analyzed quantitatively and qualitatively. The results show that students perceive the use of Wordwall as English learning media positively as it’s easy to use, it’s able to improve students’ motivation, helps understand the materials taught, and improves vocabulary mastery.  Although there are some technical challenges when using it, the students tend to prefer Wordwall and continue using it in the future. These findings confirm the potential of Wordwall as an effective learning tool in the context of English Language Teaching (ELT) in vocational schools.